PENTINGNYA PEMBENTUKAN UNDANG-UNDANG LINTAS TRANSIT DI SELAT MALAKA BAGI INDONESIA DAN MALAYSIA - Muhammad Nasir (Masalah-Masalah Hukum, 2013)
Indonesia and Malaysia are bordering contries the Malacca Strait which has been ratified by UNCLOS in 1982. Found in the UNCLOS 1982 transit Passage in the Malacca Stra;t not including the te"itorial sea, while there are parts of the territorial sea in the Malacca Strait. so that, Indonesia and Malaysia did not receive the full rights of sovereignty as the territorial sea. Transit passage only regulates passage on the high seas and EEZ. Domestic laws may not discriminate to the user states and should comply based on international law. Indonesia and Malaysia need to establish domestic laws regarding transit passage and fight back rights and responsibilities of the strait states to international community.